Norway : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the oil economy, outlook, and risk for Norway. Growth has continued to slow in the mainland economy. At the start of this year, oil prices had dropped by roughly 60 percent from their peak in June 2014 to less than USD 40 a barrel. The labor market is feeling the sting of the oil price crash. The krone has weakened substantially along with the decline in oil prices. However, a modest recovery should take root next year. Mainland economy growth should be about 1 percent this year and pick up to close to 1 3/4 percent in 2017.